Determination of Weibull Parameter by Four Numerical Methods and Prediction of Wind Speed in Jiwani (Balochistan) - Junaid K. Khan; Feroz Ahmed; Zaheer Uddin; S. Tanweer Iqbal; Saif Uddin Jilani; Afaq Ahmed Siddiqui; Asim Aijaz (Journal of Basic & Applied Sciences, 2015)
In this paper we determine the Weibull parameters (k and c) using four methods. Method of Moments, Empirical Method, Energy Pattern Method and Maximum likelihood Method have been employed to determine and compare the values of k and c. The daily wind speed data (obtained from Karachi Meteorological office) of Jiwani (Balochistan, Pakistan) town over a period of 10 years (1998-2007) is used to estimate the Weibull parameters. The mean wind speed was predicted using k and c by four methods. A significant agreement is found in measured and predicted mean wind speed.